ANALISIS STRES KERJA DAN BURNOUT TERHADAP KINERJA PERAWAT SELAMA PANDEMI COVID-19 DI RS ISLAM SURABAYA A.YANI - Gendut Sukarno; Muhammad Izzul Haq Ramadhan (STKIP Persada Khatulistiwa Sintang, 2022)
Management of human resources in the organization needs to be done as well as possible so that employee performance is good. Work stress and burnout are factors that affect performance. Job stress is a condition where tension is caused by physical and psychological imbalances that affect one's emotions, thought processes, and condition. Meanwhile, burnout arises when a person feels pressure from work. In this study there is a goal to determine the effect of work stress and burnout are factors that affect nurse performance. In early 2020, the world was shocked by the phenomenon of an epidemic originating from Wuhan, which then spread rapidly to more than 190 countries and territories affected by Covid 19. The population in the study were all nurses who were in the multazam room and shofa – marwah at home. Surabaya Islamic Hospital A. Yani, totaling 40. In this study using quantitative methods and using structural equation modeling and PLS which are used as tools of analysis. The results of the study show that work stress has a negative and significant effect on performance, burnout has a negative and significant effect on performance